2014
DOI: 10.1037/a0037321
|View full text |Cite
|
Sign up to set email alerts
|

Where’s the science? Introduction to a special issue of Canadian Psychology on science in psychology.

Abstract: The assertion that professional psychology is based on the science of psychology is embedded in the codes of ethics and standards for professional conduct of psychologists and in the accreditation criteria for professional training in psychology. However, this assertion has turned out to be far from straightforward, as indicated by the active debates in the field about the nature of psychological science, the scientific models and methods that should form the basis of psychology, the extent to which science sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…Where we stand now. The use of EBPs has become a core principle in the practice of psychotherapy over the last 15 years (Drapeau & Hunsley, 2014;Hunsley et al, 2014;Kazdin, 2008), as has the translation and implementation of research into the clini-cians' therapy rooms (Beauchamp, Drapeau, & Dionne, 2015;Stamoulos, Reyes, Trepanier, & Drapeau, 2014;Tasca, Grenon, Fortin-Langelier, & Chyurlia, 2014). Results from our investigation of psychologists and psychotherapists in independent practice in Quebec indicated that regular use of evidence-based clinical tools such as validated measures to track treatment progress (e.g., Beck Depression Inventory, Outcome Questionnaire -45 (OQ-45)), and the use of manualized treatments, established clinical guidelines, and validated assessment tools (personality inventories, formal diagnostic inventories) remains low in everyday practice (Bradley et al, in press).…”
Section: Evidence-based Practice (Ebp)mentioning
confidence: 99%
“…Where we stand now. The use of EBPs has become a core principle in the practice of psychotherapy over the last 15 years (Drapeau & Hunsley, 2014;Hunsley et al, 2014;Kazdin, 2008), as has the translation and implementation of research into the clini-cians' therapy rooms (Beauchamp, Drapeau, & Dionne, 2015;Stamoulos, Reyes, Trepanier, & Drapeau, 2014;Tasca, Grenon, Fortin-Langelier, & Chyurlia, 2014). Results from our investigation of psychologists and psychotherapists in independent practice in Quebec indicated that regular use of evidence-based clinical tools such as validated measures to track treatment progress (e.g., Beck Depression Inventory, Outcome Questionnaire -45 (OQ-45)), and the use of manualized treatments, established clinical guidelines, and validated assessment tools (personality inventories, formal diagnostic inventories) remains low in everyday practice (Bradley et al, in press).…”
Section: Evidence-based Practice (Ebp)mentioning
confidence: 99%
“…The logic of evidence-based practice is compelling (see Drapeau & Hunsley, 2014). Sound and consistent data, collected with procedures that are open to scrutiny, using consistent and validated measures, and published in venues that are peer reviewed, arguably offer the best potential method to identify, establish, and validate treatments.…”
Section: The Movement Toward Evidence-based Practicementioning
confidence: 99%
“…Because there is a perception that psychologists are expensive (with key stakeholders often referencing the cost of fee-for-service psychologists rather than publicly funded psychologists), there have been calls for health care systems to have more duties performed by less qualified and less expensive staff, which further serves to blur lines between disciplines. Major legal changes in the mental health landscape may have further complicated the situation (see Drapeau & Hunsley, 2014). In Quebec, for example, the passing of Bill 21 formerly gave the right to nonpsychologists to offer psychotherapy services and to diagnose mental disorders.…”
Section: Changes In the Society We Live Inmentioning
confidence: 99%